Human identification by lice: A Next Generation Sequencing challenge. (September 2016) - Pilli, Elena; Agostino, Alessandro; Vergani, Debora; Salata, Elena; Ciuna, Ignazio; Berti, Andrea; Caramelli, David; Lambiase, Simonetta
Highlights: Insects found at a crime scene can provide a contribution to forensic investigations. The analysis of human genetic material obtained from entomological samples is proposed. NGS technology was used to analyze human DNA from the gastrointestinal tract of lice. Lice found at the crime scenes can be valuable forensic allies. Abstract: Rapid and progressive advances in molecular biology techniques and the advent of Next Generation Sequencing (NGS) have opened new possibilities for analyses also in the identification of entomological matrixes. Insects and other arthropods are widespread in nature and those found at a crime scene can provide a useful contribution to forensic investigations. Entomological evidence is used by experts to define the postmortem interval (PMI), which is essentially based on morphological recognition of the insect and an estimation of its insect life cycle stage. However, molecular genotyping methods can also provide an important support for forensic entomological investigations when the identification of species or human genetic material is required. This case study concerns a collection of insects found in the house of a woman who died from unknown causes. Initially the insects were identified morphologically as belonging to the Pediculidae family, and then, human DNA was extracted and analyzed from their gastrointestinal tract. The application of the latest generation forensic DNA assays, such as the Quantifiler ® Trio DNA Quantification Kit and the HID-Ion AmpliSeq™ Identity Panel (Applied Biosystems ® ), individuated the presence of human DNA in the samples and determined the genetic profile.